Alteromonas Myovirus V22 Represents a New Genus of Marine Bacteriophages Requiring a Tail Fiber Chaperone for Host Recognition - Rafael Gonzalez-Serrano (American Society for Microbiology, 2020)
ABSTRACT Marine phages play a variety of critical roles in regulating the microbial composition of our oceans. Despite constituting the majority of genetic diversity within these environments, there are relatively few isolates with complete genome sequences or in-depth analyses of their host interaction mechanisms, such as characterization of their receptor binding proteins (RBPs). Here, we present the 92,760-bp genome of the Alteromonas-targeting phage V22. Genomic and morphological analyses identify V22 as a myovirus; however, due to a lack of sequence similarity to any other known myoviruses, we propose that V22 be classified as the type phage of a new Myoalterovirus genus within the Myoviridae family. V22 shows gene homology and synteny with two different subfamilies of phages infecting enterobacteria, specifically within the structural region of its genome. To improve our understanding of the V22 adsorption process, we identified putative RBPs (gp23, gp24, and gp26) and tested their ability to decorate the V22 propagation strain, Alteromonas mediterranea PT11, as recombinant green fluorescent protein (GFP)-tagged constructs. Only GFP-gp26 was capable of bacterial recognition and identified as the V22 RBP. Interestingly, production of functional GFP-gp26 required coexpression with the downstream protein gp27. GFP-gp26 could be expressed alone but was incapable of host recognition. By combining size-exclusion chromatography with fluorescence microscopy, we reveal how gp27 is not a component of the final RBP complex but instead is identified as a new type of phage-encoded intermolecular chaperone that is essential for maturation of the gp26 RBP. IMPORTANCE Host recognition by phage-encoded receptor binding proteins (RBPs) constitutes the first step in all phage infections and the most critical determinant of host specificity. By characterizing new types of RBPs and identifying their essential chaperones, we hope to expand the repertoire of known phage-host recognition machineries. Due to their genetic plasticity, studying RBPs and their associated chaperones can shed new light onto viral evolution affecting phage-host interactions, which is essential for fields such as phage therapy or biotechnology. In addition, since marine phages constitute one of the most important reservoirs of noncharacterized genetic diversity on the planet, their genomic and functional characterization may be of paramount importance for the discovery of novel genes with potential applications.